Electronics : Basic, Analog, and Digital with PSpice. - Sabah, Nassir H. (CRC Press, 2009)
Preface Foreword: Brief History and Impact of Electronics Convention for Symbols Basic Diode Circuits Overview Learning Objectives Ideal and Practical Diodes Ideal Diode Ideal Si pn Junction Diode Practical Diodes Incremental Diode Resistance Basic Analysis of Diode Circuits Piecewise Linear Approximation Bias Point Small-Signal Model Rectifier Circuits Half-Wave Rectifier Full-Wave Rectifier Smoothing of Output Capacitor-Input Filter Approximate Analysis of Capacitor-Input Filter Zener Voltage Regulator Voltage-Current Characteristic Analysis of Zener Regulator Load regulation and Line Regula.